Peningkatan Keterampilan Menggosok Gigi Anak Tunagrahita Kategori Sedang Melalui Metode Drill di SLB Wiyata Dharma 3 Ngaglik - Indro Purnomo; Betty Kusumaningrum (Universitas Sarjanawiyata Tamansiswa, 2022)
Children with mental retardation are having limitations in terms of self-development, one of which is the skill of brushing teeth. This study aims to improve the self-development skills of brushing the teeth of moderately mentally retarded children through the drill method on the 3rd grade of Sekolah Luar Biasa (SLB) Wiyata Dharma 3 Ngaglik. With the drill method, children with moderate mental retardation are accustomed to brushing their teeth repeatedly so that children with moderate mental retardation can understand and have skills in brushing their teeth without needing help from others. This research is a classroom action research using Kemmis and Mc. Taggart which consists of 4 stages including planning, implementing actions, observing and reflecting. The implementation of this research by providing action in 2 cycles. The research subjects were 2 students with moderate mental retardation of the 3rd grade on Sekolah Dasar Luar Biasa Wiyata Dharma 3 Ngaglik, who were 10 years old and male. Collecting data using action test and observation techniques. The technique of analyzing the data uses quantitative descriptive. The results showed that the self-development skills of brushing teeth in moderately mentally retarded children could be improved through the drill method. The increase was obtained by (1) habituation and guidance intensely in each activity, (2) utilizing visual media assistance (3) adding students' favorite activities as a reward so that students actively participate in learning.